Influence of Lithium and Lanthanum Treatment on TiO2 Nanofibers and Their Application in n‐i‐p Solar Cells. Issue 14 (24th June 2019) - Ambroz, Filip; Sathasivam, Sanjayan; Lee, Roxanna; Gadipelli, Srinivas; Lin, Chieh‐Ting; Xu, Shengda; Poduval, Radhika K.; Mclachlan, Martyn A.; Papakonstantinou, Ioannis; Parkin, Ivan P.; Macdonald, Thomas J.
Abstract: Invited for this month's cover picture is the group of Dr. Macdonald from the Department of Chemistry at University College London (UK). The cover picture shows a scanning electron microscopy image of lanthanum‐treated TiO2 nanofibers rendered to show a three‐dimensional representation of the nanostructured solar cell. This work shows that the addition of lithium and lanthanum cations causes minimal substitutional or interstitial doping of TiO2 nanofibers. In a solar cell, photovoltaic characteristics reveal that lanthanum treatment is beneficial, whereas lithium treatment is found to be detrimental to the device performance for both dye‐sensitized and perovskite solar cells. Read the full text of the Article at 10.1002/celc.201900532 . Abstract : "The addition of lithium and lanthanum cations is shown to cause minimal substitutional or interstitial doping of TiO2 . Brunauer–Emmett–Teller measurements show that lanthanum‐treated TiO2 nanofibers had an increase in surface area, which even exceeded that of TiO2 P25 nanoparticles. Finally, treated and untreated TiO2 nanofibers are used in n‐i‐p solar cells. Photovoltaic characteristics reveal that lanthanum treatment is beneficial, whereas lithium treatment is found to be detrimental to the device performance for both dye‐sensitized and perovskite solar cells…" Learn more about the story behind the research featured on the front cover in this issue's Cover Profile. Read the corresponding Article at 10.1002/celc.201900532 .